The English Language Expressions Used by Indonesian Students to Talk to English Native Speakers - Anggi Putri Ulfia Putri Ulfia; Sudirman; Utep Sobali; Kania Farida (JOLADU: Journal of Language Education, 2024)
This study aims to provide a comprehensive understanding on how the Indonesia students speak to English native speaker. This study used literatures review study to review the expressions used and problems that are faced by Indonesian-by-Indonesian students to talk to English native speakers. The challenges faced by Indonesian students when they practice speaking English with native speakers are pronunciation difficulties, grammar mistakes and lack of confidence in speaking English. Pronunciation practice exercises can benefit individuals looking to improve their overall language skills. By focusing on correct pronunciation, students can enhance their clarity and understanding when communicating with others. grammar practice can help individuals avoid common errors that may hinder their overall language fluency. Overall, a combination of pronunciation and grammar practice exercises can greatly benefit individuals seeking to enhance their language skills and become more confident communicators. If all of challenges in both pronunciation and grammar are able to overcome, they can cover the problem of lack of confidence in speaking English that makes students feel hesitant to speak up in class or engage in conversations with native English speakers